Rare Kelangon The Innovation Of Gender Wayang Colosal For Children - Ni Ketut Suryatini; Nyoman Lia Susanthi (Institut Seni Indonesia Denpasar, 2019)
Indonesia is a country with a high level of cultural heterogeneity. In accordance with the State of the Republic of Indonesiaâ€™s President Joko Widodo, the country needs disruptive innovations. Disruptive innovation reverses the impossibility into opportunities and results intransformative value for the Indonesian people and nation. Disruptive innovation can also be applied in the arts. Moreover, amid the setbacks in the ethical and moral values â€‹â€‹of the Indonesian nation, art offers a way to shape character. One of the Balinese arts which has succeeded in changing the character is the art of Balinese traditional music. The tradition of storytelling, traditional childrenâ€™s games and songs (gending) Bali is needed in upholding moral values â€‹â€‹and character education early on. For this reason, the creation of the â€œRare Kelangonâ€ which has been tested by the international public at the Cultural Performance at the IMF in Nusa Dua Bali on October 11, 2018 and the 24th National Education Day on August 25, 2019. The method used in creating this music innovative of Gender wayang was the research and development of Brog and Gall combined with Bandem and Sutejaâ€™s Balinese art creation method. There are 8 stages of creations, namely ngerencana,nuasen, makalin, refinement of the initial product, ngebah I, revision of the final refinement and ngebah II. The results of the study found that the innovations which made in the creation of Rare Kelangon works were extension types, which the invention of the development of existing products, added so that it becomes something new and valuable. The gender wayanggamelan has existed before, but to revive the genderwayang songs, a component of work which also needs to be preserved is gending rare (traditional childrenâ€™s songs), traditional games, and satua (fairy tales) of the Balinese people who are also full of values â€‹â€‹of character education.